2021
DOI: 10.1002/cbdv.202100679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pomelo Seed Extracts as Natural Antioxidant, Antibacterial, Herbicidal Agents, and Their Functional Components

Abstract: Pomelo seeds (PS) are important by-product of pomelo fruits (Citrus grandis Osbeck). The value-added utilization of PS remains highly challenged. This study aimed to investigate the utilization potential of PS as natural antioxidant, antibacterial, herbicidal agents, and their functional components. The ethanolic extract (EE) of PS and its four fractions as PEE (petroleum ether extract), AcOEtE (ethyl acetate extract), BTE (butanol extract), and WE (water extract), were prepared and biologically evaluated. BTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Hesperetin has antioxidant activity. Restraining or eliminating the priming or reproduction of superfluous active substances can postpone or inhibit cell injury caused by physiological oxidants and decrease the risk of potential human health influence related to oxidative stress or free radicals [ 23 , 26 ]. It is significant to measure the antioxidant activity of hesperetin derivatives in the exploration of their potential applications in the food, pharmaceutical, or cosmetics industries.…”
Section: Resultsmentioning
confidence: 99%
“…Hesperetin has antioxidant activity. Restraining or eliminating the priming or reproduction of superfluous active substances can postpone or inhibit cell injury caused by physiological oxidants and decrease the risk of potential human health influence related to oxidative stress or free radicals [ 23 , 26 ]. It is significant to measure the antioxidant activity of hesperetin derivatives in the exploration of their potential applications in the food, pharmaceutical, or cosmetics industries.…”
Section: Resultsmentioning
confidence: 99%
“…Each of the variables was represented by a vector, the direction and length of which indicated the contribution of variables. [43] PC1 explained 46.8 % of the variability, and was positively associated with all feature vectors but E. coli inhibition (ECI). Among them, DPPH, FRAP, TFC, ABTS and TPC had high load, indicating that the test samples in this study had the most outstanding application potential in antioxidant.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…(2022) reported that the Majia pomelo seed oil had 39.32% lipid mainly composed of linoleic acid and oleic acid, and was not toxic to normal liver LO2 cells. In one of our previous studies, the ethyl acetate extract from pomelo seed was found to exhibit good antioxidant and herbicidal activities and contain naringin, deacetylnomilin, limonin, nomilin, and obacunone as its main components ( Ling et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%